2021
DOI: 10.1186/s13023-021-01735-2
|View full text |Cite
|
Sign up to set email alerts
|

No evidence for preferential X-chromosome inactivation as the main cause of divergent phenotypes in sisters with X-linked hypohidrotic ectodermal dysplasia

Abstract: Background X-linked hypohidrotic ectodermal dysplasia (XLHED), a rare genetic disorder, affects the normal development of ectodermal derivatives, such as hair, skin, teeth, and sweat glands. It is caused by pathogenic variants of the gene EDA and defined by a triad of hypotrichosis, hypo- or anodontia, and hypo- or anhidrosis which may lead to life-threatening hyperthermia. Although female carriers are less severely affected than male patients, they display symptoms, too, with high phenotypic v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…It has been reported that the HED phenotype in EDA female carriers is not correlated with the XCI pattern [ 28 ]. Laura et al found that women with mild HED did not have higher non-randomized XCI ratios and that there was no significant correlation between tilted XI ratios and XLHED phenotypic expression levels [ 29 ]. In this study, patient #35 showed extremely skewed (98:2) XCI, and patients #347 and #204 showed moderately skewed (21:79 and 30:70) XCI.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the HED phenotype in EDA female carriers is not correlated with the XCI pattern [ 28 ]. Laura et al found that women with mild HED did not have higher non-randomized XCI ratios and that there was no significant correlation between tilted XI ratios and XLHED phenotypic expression levels [ 29 ]. In this study, patient #35 showed extremely skewed (98:2) XCI, and patients #347 and #204 showed moderately skewed (21:79 and 30:70) XCI.…”
Section: Discussionmentioning
confidence: 99%
“…A high degree of inter-and intrafamilial variability of symptoms among affected females has been observed. 24 Females are sometimes only recognized to be carriers of XLHED when they have siblings with the condition. 25 Sons of female carriers-if affected-are likely to show a more severe phenotype than their mothers.…”
Section: Discussionmentioning
confidence: 99%
“…Heterozygous females are usually not as severely affected by XLHED as hemizygous males. A high degree of inter‐ and intrafamilial variability of symptoms among affected females has been observed 24 . Females are sometimes only recognized to be carriers of XLHED when they have siblings with the condition 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Our finding, therefore, suggests that skewed X inactivation cannot account for the mild presentation of CFNS in one of our twin sisters and probably other mildly affected female individuals. Recently, another research group did not find evidence for preferential XCI or a distinct correlation between XCI ratios in a group of familial X-linked hypohidrotic ectodermal dysplasia patients showing variable disease manifestation [ 21 ]. Hence our result strengthens the above conclusion regarding the presence of additional yet undetected modifying factors resulting in discordant phenotype in X-linked disorders.…”
Section: Discussionmentioning
confidence: 99%